KINERJA PENYULUH PERTANIAN DALAM MENDUKUNG PERTANIAN RAMAH LINGKUNGAN DI DESA BONTOMANAI KECAMATAN BANGKALA KABUPATEN JENEPOTO (Performance of Agricultural Extension Workers in Supporting Environmentally Friendly Agriculture in Bontomanai Village, Bangkala District, Jeneponto Regency) - IRMAWATI IRMAWATI; SYAFIUDDIN SALEH; AKBAR AKBAR (Universitas Mulawarman (University of Mulawarman), 2022)
This study aims to determine the performance of extension workers in supporting environmentally friendly agriculture in Bontomanai Village, Bangkala District, Jeneponto Regency. This research was conducted in June- August 2022. The sampling technique was chosen at random simple random sampling, namely a sample taken of 10% or as many as 20 farmers. The data analysis used in this study was a likert scale analysis. The results showed that the performance of agricultural extension workers in supporting environmentally friendly agriculture was: a) the preparation of the main activities of environmentally friendly agricultural extension workers 83.67% with excellent descriptions, b) Compiling periodic meeting schedules in environmentally friendly agriculture 71.33% with good descriptions, c) Develop the establishment of natural agricultural institutions at the farmer level 76% with good descriptions and d) Facilitate the development of farmer information media related to environmentally friendly agriculture to disseminate agricultural extension information 80.33% with excellent descriptions so that the average used in measuring the performance of agricultural extension workers in supporting environmentally friendly agriculture in Bontomanai Village, Bangkala District, Jeneponto Regency is 77.83 with good descriptions.